Development and psychometric evaluation of the MetabQoL 1.0: a quality of life questionnaire for paediatric patients with intoxication-type inborn errors of metabolism - Zeltner, Nina Amélie; Bondarenko, Aljona; Kölker, Stefan; Burgard, Peter (JIMD reports, 2017)
Introduction: This study is part of the “European network and registry for intoxication type metabolic diseases” (E-IMD) project. Intoxication-type inborn errors of metabolism (IT-IEM) such as urea cycle disorders (UCD) and organic acidurias (OA) have a major impact on patients’ lives. Patients have to adhere to strict diet and medication and may suffer from metabolic crises and neurocognitive impairment. Disease-specific health-related quality of life (HrQoL) assessment questionnaires are the method of choice to estimate the subjective burden of a disease. To date, no such instrument is available for IT-IEM. Methods: Disease-specific patient- and parent-reported HrQoL questions were constructed in German based on focus group interviews with patients and parents. Questionnaires for patients from 8 to 18 years were piloted with 14 participants (n = 9 children and adolescents, n = 5 parents) by cognitive debriefing and tested psychometrically with 80 participants (n = 38 patients, n = 42 parents) for item characteristics, validity, and reliability to construct the first version of a disease-specific HrQoL questionnaire. Results: Twenty-eight questions were selected based on item descriptives. Scales of self- and proxy questionnaires demonstrated acceptable to excellent reliability in terms of internal consistency (Cronbach’s α = 0.70-0.93). Scales and total scores correlated with those of generic HrQoL questionnaires, showing convergent validity. Discussion: The MetabQoL 1.0 questionnaire exhibits sound psychometric properties and is a promising step towards assessing patient-reported outcomes in research and clinical practice. It provides a solid basis for translation into other languages and further elaboration and psychometric exploration in larger populations.
Gesehen am 24.07.2018